Ruang Pemolisian pada Media Sosial: Sebuah Tantangan dan Kebutuhan - Mujab, Saeful (Jurnal Keamanan Nasional, 2019)
The purpose of this study is to find out what the police need in facing the challenges of policing in the social media space. The development of social media on the one hand provides benefits for human life, but social media is also used as an instrument of crime. For example, hoaxes, pornography, online prostitution, and hate speech. Therefore, the large number of users of social media and interactions on existing social media, gives birth to new problems and challenges in handling order and security. This study uses a literature review approach or research fundamentals with a focus on the keywords policing and social media.